Online liquor gets audited: a review of regulatory controls and supply practices of online liquor retailers in NSW, Australia - Jonathon Noyes; Melissa Palermo; Arlita Willman |; Jenna Harkness; Rachel Bienenstock; Paul Klarenaar (Sax Institute, 2022)
Objectives: In New South Wales (NSW), Australia, the number of 'online liquor licences' - packaged liquor licences with conditions restricting the sale of alcohol to online, phone or fax orders - increased from 101 in 2010 to 500 by May 2018. International and national evidence is emerging that this growth in online liquor licences has been accompanied by increased risk of supply to young and intoxicated people. This study aimed to determine the extent to which online liquor retailers in NSW have adopted safeguards to prevent people younger than 18 years purchasing alcohol online; and the supply of alcohol to intoxicated people. It also aimed to assess the regulatory framework in NSW for these licences. Methods: We undertook an audit between May and November 2018 of regulatory controls for 213 online liquor retailers in NSW with publicly available websites at the time of auditing. A comparative analysis of the NSW Liquor Act 2007 and the NSW Liquor Regulation 2018 was conducted. Results: Three gaps in the existing legal safeguards for online liquor retailers were identified: inconsistent application of the NSW Liquor Act 2007; the inability of the regulator to complete compliance auditing; and an absence of consistent mandatory signage. The study also identified inconsistencies between the regulation of physical and online liquor retailers. Conclusions: Study findings led to the formulation of recommendations for regulatory change, which were presented to the government oversight agency, Liquor & Gaming NSW, in April 2019 and followed up by written submissions from the research group on behalf of Northern Sydney Local Health District Health Promotion. Several key reforms were subsequently incorporated into the NSW Liquor Amendment (24-hour Economy) Bill 2020. Findings have informed an advocacy approach which has led to improved regulatory reform within NSW.